Consensus of fractional-order multi-agent systems via current and time-delay states feedback. Issue 10 (27th July 2022) - Pan, Huan; Yu, Xinghuo; Guo, Ling; Xue, Li
Abstract : The consensus problems of fractional-order multi-agent systems(FOMAS) are investigated under a fixed interaction graph. A consensus protocol that has current and time-delay states is designed. The conception of practical consensus of FOMAS is proposed. The asymptotical consensus condition is obtained by taking advantage of Laplace transform. Furthermore, the practical consensus condition of the FOMAS with the protocol is given by direct derivation. Through numerical simulation, we find that the standard control protocol can not achieve consensus in some situations. However, the proposed protocol could make the states of multi-agent be consensus or even practical consensus.